Deliberation and governance in Chinese middle-class neighborhoods. (16th November 2018) - Tang, Beibei
Abstract: This paper examines the mechanisms of deliberation and conflict resolution in Chinese urban middle-class residential communities. Along with the rise of private home ownership and urban middle-class residential estates, disputes and conflicts have risen between the residents, resident self-elected organization (homeowner associations), real estate developer and property management companies, and the local government. Through the lens of deliberation in middle-class neighborhoods, this paper analyzes (1) how and to what extent deliberation is introduced and employed as an instrumental tool by the local government to achieve their goal of maintaining social stability. (2) In what ways and to what extent deliberation has served as part of governance strategies. And (3) whether and how the state and non-state actors interact with each other during this process to produce more democratic governance under the Party-state's authoritarian rule. This paper adopts a systemic approach to examine authoritarian deliberation as a neighborhood governance strategy. The findings suggest that (1) deliberation has become an instrumental tool for conflict resolution introduced by the local government to middle-class neighborhoods. Residents' Committees, on behalf of the state, has become key coordinator and mediator during the deliberation process. (2) The systemic approach of authoritarian deliberation includes a mix of deliberative elements and other features of political culture, traditions, strategies, and institutions. The dynamic interactions between deliberation and authoritarianism, between deliberative and non-deliberative features, and between formal deliberative meetings and informal deliberative talks all contribute to a functional deliberative system.